Psychology and Islamic Law in the Inong Balee Tradition: Narratives of Forgiveness in the Aceh Conflict - Fahmi, Khairul; Fadlullah, Nyak (UIN K.H. Abdurrahman Wahid Pekalongan, 2024)
This article examines the narrative of forgiveness delivered by Inong Balee after the Aceh conflict through the lens of Psychology and Islamic law. This research contributes to the study of the continuity of the concept of forgiveness in the context of conflict in Indonesia. This qualitative research was conducted intensively for three months. The data was collected by interviewing two Inong Balee and supported by adequate literature data. The results showed that the forgiveness done by the Inong Balee was conditional. Religious values, community social interactions, and victims' problems during the conflict influence conditional forgiveness. Furthermore, conditional forgiveness becomes a transformative attitude for Inong Balee in fulfilling the rights of conflict victims.